1953
DOI: 10.1113/jphysiol.1953.sp004876
|View full text |Cite
|
Sign up to set email alerts
|

Responses of muscle blood vessels to intra‐arterially and intravenously administered noradrenaline

Abstract: (0-2-0-4jug/kg/min), unanaesthetized dog). A transient dilatation followed by constriction has been observed by Wakim & Essex (1952, dog), and Imig et al. (1952, 2p,g/kg body weight, unanaesthetized dog).We have compared the action ofintra-arterial and intravenous noradrenaline on the blood vessels of the skeletal muscle of the anaesthetized cat. The responses differed, but an adequate explanation capable of experimental proof has been obtained. METHODBlood flow in response to noradrenaline was studied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1954
1954
1986
1986

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…For example, it has been demonstrated that intravenous infusions of noradrenaline increase popliteal efferent lymph flow in sheep (McHale & Roddie, 1983a) and although noradrenaline is known to depress blood flow (Barcroft, Gaskell, Shepherd & Whelan, 1954;Green, Deal, Bardhanabaedya & Denison, 1955;Green & Kepchar, 1959) (and presumably lymph production) in the tissues drained by this lymph duct, the uncertainty remains that the increased lymph flow could have been a passive consequence of raised arterial pressure since there is evidence that intravenous noradrenaline infusions can transiently increase blood flow secondary to arterial pressure elevation (Cobbold & Vass, 1953). It has been possible in the present study to examine the effect of noradrenaline on lymphatic pumping with the ambiguity of its effect on lymph formation removed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that intravenous infusions of noradrenaline increase popliteal efferent lymph flow in sheep (McHale & Roddie, 1983a) and although noradrenaline is known to depress blood flow (Barcroft, Gaskell, Shepherd & Whelan, 1954;Green, Deal, Bardhanabaedya & Denison, 1955;Green & Kepchar, 1959) (and presumably lymph production) in the tissues drained by this lymph duct, the uncertainty remains that the increased lymph flow could have been a passive consequence of raised arterial pressure since there is evidence that intravenous noradrenaline infusions can transiently increase blood flow secondary to arterial pressure elevation (Cobbold & Vass, 1953). It has been possible in the present study to examine the effect of noradrenaline on lymphatic pumping with the ambiguity of its effect on lymph formation removed.…”
Section: Discussionmentioning
confidence: 99%
“…Isopropylnoradrenaline is, however, much the more powerful dilator, causing sustained dilatation even after intra-arterial administration, whereas comparable doses of adrenaline produce only transient increases in flow (Barcroft & Swan, 1953). The action of isopropylnoradrenaline contrasts strikingly with that of noradrenaline, which has a marked constrictor effect on the blood vessels of muscle (Barcroft & Konzett, 1949;Cobbold & Vass, 1953).…”
Section: F7mentioning
confidence: 94%
“…The possibility cannot be ruled out, however, that increased lymph flow was a passive consequence of increased arterial pressure. There is evidence that intravenous noradrenaline infusions can produce a transient increase in blood flow which can be prevented by inserting a pressure compensator, indicating that it results from the increased arterial pressure (Cobbold & Vass, 1953). An increased blood flow of this type does not readily explain the lymph flow changes in the present study since their onset was too rapid.…”
Section: Discussionmentioning
confidence: 99%